APPLICATION OF PROJECT-BASED LEARNING-BASED E-MODULE TO STUDENT LEARNING OUTCOMES IN 21ST CENTURY BIOLOGY LEARNING - Wally, Pramita (International Research of Multidisciplinary Analysis, 2024)
The application of information and communication technology in the learning process must be modified to answer global demands as a response to the needs of the industrial revolution in the 21st century, where humans and technology are aligned to create new opportunities creatively and innovatively. One form of learning modification is by designing learning media that attracts students' interest in learning so that their learning outcomes are maximized. E-module is one of the teaching media which is a multimedia development solution to facilitate students' understanding in today's learning. The purpose of this study is to determine the effect of implementing e-modules based on project based learning on student learning outcomes. This type of research is quantitative research using pre-experimental design with one group pretest-posttest design. The sample in this study was a 3rd semester biology class consisting of 20 students. The types of research instruments used were questionnaires and essay tests. The data found were then analyzed using the normalized N Gain test to determine the effectiveness of the application of e-modules on student learning outcomes with the help of the SPSS version 23 application. The results of the study showed that the N-Gain value was 66.78, which means that the application of e-modules based on project based learning is quite effective on student learning outcomes